Nivel de comunicación asertiva docente frente a la mejora convivencial (2020)
Teachers, in addition to the emotional burden of accompanying a diversity of students with very particular situations and institutional requirements related to academic performance, must present difficulties for the communication of feelings, that is, they demonstrate deficiencies in social skills in interaction with members of your community; hence the deficit to intervene assertively in processes related to conflict and coexistence, since they are evidenced from the instrument of Self-assertiveness and hetero-assertiveness that reflect emotional behaviors in the order of aggressive behaviors with 74.9% in the AA variable; while 49% is located in the dimension of social relations and behaviors HA. The implications of the data corroborate that the “Style of social interaction characterized by high Self-assertiveness and low hetero-assertiveness. It is characteristic of people who consider themselves superior or better than others, whom they tend to belittle”; that is, they show aggressive behaviors and a slight sample of assertiveness contained in the HA variable does not reach 50%. From the objectives that were postulated in the research work, this is of a non-experimental type of cross-sectional or transactional because the application or capture of the information was carried out in a single moment. Hernández. (2014